Becoming Asustado (Scared): An Ethnographic Contribution to a Transdisciplinary Approach to Children’s Health and Development - Remorini, Carolina (2020)
We characterized and analyzed women’s narrative around the idea of becoming asustado (scared) as a cultural way of understanding why children get sick repeatedly or develop illnesses that become increasingly severe, as part of a study carried out in rural communities from the Molinos District, in the North-West of Argentina. We analyze and discuss the implications of becoming asustado for everyday child-rearing and children's health, sociability, and performance in different community endeavors from ethnographic data. We intentionally selected 15 cases elaborated based on 55 semi-structured interviews with 15 women, between 25 and 55 years old, all caregivers of children under 6 years old. Our results show that susto (fright) serves as an explanation for those people who do not fit with cultural expectations about their phenotype and social performance. Also, it is a culturally acceptable way of dealing with both physical and mental stress.